Strategic analysis in support of international policy making case studies in achieving analytical relevance - Juneau, Thomas (Rowman & Littlefield, 2017)
Broader thematic reflections on strategic analysis are combined with innovative case studies of how organizations have worked to successfully produce relevant analysis. The first section of the book explores challenges to achieving relevance at the level of the analyst, while the remainder of the book analyses cases at the level of organizations